"A Lantern for the Soul": a Translation and Study of Quṭb al-Dīn Nayrīzī’s Sharḥ Duʿāʾ al-ṣabāḥ - Izzo, Gianni (Journal of Sufi studies, 2025)
This article offers an English translation of a Persian commentary (sharḥ) on a Shiʿi supplication (duʿāʾ) by Sayyid Quṭb al-Dīn Muḥammad Nayrīzī, thirty-second leader of the Shiʿi-Sufi Ẕahabiyya order. Nayrīzī’s commentary on "The Morning Supplication" (Duʿāʾ al-ṣabāḥ), traditionally attributed to ʿAlī b. Abī Ṭālib, recasts the Arabic text into a sequence of Persian quatrains, retaining its sacred authority while giving it new life in the poetic and didactic world of Persian verse. I begin with an overview of Nayrīzī’s background and influences before examining the main themes of his commentary. I then explore how core Sufi concerns - above all the supplicant’s absolute dependence on God’s mercy - are woven into an established genre of Shiʿi devotion. For Nayrīzī, duʿāʾ is a "door of entreaty," a portal to mercy and a bulwark against the caprice of the self. In his verses, prayerful utterance and mystical insight converge to convey a devotional vision grounded in the sanctified speech of a Shiʿi Imam. Supplication commentaries such as this thus function as acts of theological reflection and as poetic works that heighten the emotional and aesthetic registers of Islamic piety.